Penerapan Kelas Digital Edmodo untuk Meningkatkan Minat Belajar dan Hasil Belajar Siswa - Dewi Hastaty Lanusi (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objectives were to improve the children’s interest and outcomes in natural science through Edmodo digital learning. A classroom action research with two cycles was implemented to twenty sixth grade children at Public Elementary School 86 Kota Tengah, Gorontalo Province. Data were collected in each phase, namely, planning, action, observation and evaluation, reflection. Data were analysed descriptively and quantitatively. Results show that the children’s interest was improved 50% and their learning outcomes 72 despite below the minimum mastery level in cycle 1. Whereas, their interest was improved to 78.5% and their learning outcomes to 88.0 in cycle 2.